PELESTARIAN KEARIFAN LOKAL: TARI DAN MUSIK KERAMBA APUNG SEBAGAI MEDIA EDUKASI BUDAYA DI DESA ARO, BATANG HARI - Finata, Duwi; Maresya Suryaningrum, Bunga; Tsabitha Amanda, Charenina; Hepi Andini, Sintia; Harmuli, Sri; Novitasar, Novitasar; Umu Aimanah, Faizati; Khatimah, Husnul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Preserving local wisdom is an important part of maintaining the cultural identity of a region. In Aro Village, Batanghari, Keramba Apung dance and music are one of the artistic expressions that reflect the life of coastal communities. This art not only functions as entertainment, but also as a medium for cultural education for the younger generation. This article discusses the role of Keramba Apung dance and music in preserving local wisdom and its potential as a means of cultural education in Aro Village. With a qualitative approach through observation and interviews with local artists, this study reveals the philosophical values, history, and development strategies for this art so that it remains sustainable amidst the flow of modernization. The results of the study show that Keramba Apung dance and music contain educational values ​​that teach about harmony with nature, social solidarity, and respect for ancestral heritage. Therefore, efforts to preserve this art need support from the local government, cultural communities, and educational institutions so that it remains alive and develops as the cultural identity of Aro Village.